Customary Rights Versus Land Use Rights - Pasamai, Syamsuddin; Salle, Salle (Devotion : Journal of Research and Community Service, 2024)
The 1945 Constitution, Article 33 paragraph (1) grants the State the authority to regulate and manage natural resources, including land, for the welfare of the people. This authority is further elaborated in the Basic Agrarian Law (UUPA), which establishes regulations concerning land ownership, utilization, and management. The UUPA recognizes the state's right of control (recht van beschikking), customary land rights (hak ulayat), and land use rights for business purposes. However, these rights must align with the principle of prioritizing the public interest. In practice, the subordination of customary rights and land use rights to public interest policies can potentially lead to conflicts and economic losses for the rights holders. Issues such as inadequate compensation, lack of consultation, and improper recognition of customary rights often arise, particularly in regions where land is closely tied to indigenous traditions and livelihoods. To address these concerns, there is an urgent need for a standardized regulatory framework that balances the principle of public interest with the protection of customary rights and business land use rights. Such a framework should ensure legal certainty, equitable compensation, and mechanisms for conflict resolution to prevent injustice. By harmonizing state authority with individual and communal rights, the regulation can contribute to sustainable land management while upholding justice and public welfare. This study highlights the importance of legal reform to create comprehensive and inclusive land policies that safeguard the rights of all stakeholders.